Dual‐time‐point 64Cu‐PSMA‐617‐PET/CT in patients suffering from prostate cancer. (17th June 2019) - Hoberück, Sebastian; Wunderlich, Gerd; Michler, Enrico; Hölscher, Tobias; Walther, Martin; Seppelt, Danilo; Platzek, Ivan; Zöphel, Klaus; Kotzerke, Jörg
Abstract : Regardless of its high positron energy, 68 Ga‐labeled PSMA ligands have become standard of care in metabolic prostate cancer imaging. 64 Cu, a radionuclide with a much longer half‐life (12.7 h), is available for PSMA labeling allowing imaging much later than 68 Ga. In this study, the diagnostic performance of 64 Cu‐labeled PSMA was compared between early and late scans. Sixteen men (median age: 70 y) with prostate cancer in different stages underwent 64 Cu‐PSMA‐617‐PET/CT 2 and 22 hours post tracer injection. Pathologic and physiologic uptakes were analyzed for both points of time. Pathologic tracer accumulations occurred in 12 patients. Five patients presented with pathologic uptake in 17 different lymph nodes, two patients showed pathologic bone uptake in nine lesions, and seven patients had pathologic PSMA uptake in eight prostatic lesions. Physiologic uptake of the renal parenchyma, urine bladder, and salivary glands decreased over time, while the physiologic uptake of liver and bowel increased. In the present study, 64 Cu‐PSMA‐617‐PET demonstrated to be feasible for imaging prostate cancer for both the primary tumor site and metastases. Later imaging showed no additional, clinically relevant benefit compared with the early scans. At least the investigated time points we chose did not vindicate the additional expenditure. Abstract : 64 Cu, a radionuclide with a much longer half‐life (12.7 h), is available for PSMA labeling, allowing imaging much later and in a higher spatial resolution than 68 Ga‐PSMA. In the present study, the diagnostic performance of 64 Cu‐PSMA‐617 in early (2 h pi) and delayed (22 h pi) scans was compared in patients suffering from prostate cancer in different stages.